DEVELOPMENTAL EDUCATIONAL THEORY AND THE TEACHING OF TEAM SPORTS - VOLLEYBALL (Fiep Bulletin - online, 2011)
This paper aimed to relate the theory of teaching with the developmental process of teaching and learning team sports - volleyball. For this teaching perspective it is expected that learners are appropriating the core concepts of the sport, to make generalizations for the learning of secondary attributes of the game, demonstrating autonomy and development capabilities of their own reasoning.